Intestinal obstruction in pediatrics: Case series of unusual causes: Pediatric Intestinal Obstruction - Elghazeery, Mohamed Ahmed; Abo-Sherief , Ahmed Mohsen; Elsharaby, Ahmed Mahmoud; Arafa , Mohamed Ahmed; Elshimy, Khalid Mohamed (Iranian Journal of Pediatric Surgery, 2024)
Introduction Congenital anomalies are main cause of intestinal obstruction that occur from neonates to adults. Frequently, obstruction is due to either incarcerated hernia, adhesive bands, volvulus and intussusception. we illustrate all demographic & clinical data, imaging, surgical approach and outcome of unusual causes of pediatric intestinal obstruction. Methods We document a retrospective review of ten pediatric cases of acute intestinal obstruction for whom surgery was indicated and showed rare causes and pathology between 2020 and 2023. Results On exploration, first and second patient had non-Hodgkin intestinal lymphoma. Third case had a large polyp of Peutz– Jeghers syndrome as a nidus for jejunojejunal intussusception. Fourth patient had jeujunogastric intussusception whereas fifth case had chylous cyst, in the sixth patient, cecal duplication cyst was a cause of intussusception. Seventh case had volvulus of small gut due to entrapment through a mesenteric defect was detected whereas eighth case had ileal gel ball, ninth case had volvulus on top of mesenteric lymphangioma and tenth case had huge mesenteric chylous cyst. All causes of obstruction are rare either as a pathology or its age or presentation. Conclusion Suspicion, careful evaluation, and tailoring of appropriate treatment are corner stone for precise management of these unusual cases.